2017
DOI: 10.1186/s12913-017-2538-z
|View full text |Cite
|
Sign up to set email alerts
|

Trends in substance use admissions among older adults

Abstract: BackgroundSubstance abuse is a growing, but mostly silent, epidemic among older adults. We sought to analyze the trends in admissions for substance abuse treatment among older adults (aged 55 and older).MethodsTreatment Episode Data Set - Admissions (TEDS-A) for period between 2000 and 2012 was used. The trends in admission for primary substances, demographic attributes, characteristics of substance abused and type of admission were analyzed.ResultsWhile total number of substance abuse treatment admissions bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 18 publications
5
53
0
2
Order By: Relevance
“…By 2030, one-fifth of the United States population will be 65 years or older (Mather et al, 2015). Coinciding with the aging population is an increase in the number of older people using drugs of abuse (Chhatre et al, 2017; Duncan et al, 2010; Han et al, 2009; White et al, 2011). The increase of older drug users appears primarily attributable to aging of the “baby boomers”, who represent some 21% of past-month drug users (SAMSHA, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By 2030, one-fifth of the United States population will be 65 years or older (Mather et al, 2015). Coinciding with the aging population is an increase in the number of older people using drugs of abuse (Chhatre et al, 2017; Duncan et al, 2010; Han et al, 2009; White et al, 2011). The increase of older drug users appears primarily attributable to aging of the “baby boomers”, who represent some 21% of past-month drug users (SAMSHA, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The above issues are particularly relevant to cocaine use. From 2000 to 2012, the number of cocaine users aged 55 or older presenting for drug treatment in the US increased by 63% (Chhatre et al, 2017). Cocaine is one of the most commonly used drugs in 50 to 59-year-old people in treatment for substance use disorders (Wu and Blazer, 2011), and older cocaine users are more likely than their younger counterparts to smoke cocaine (Martin et al, 2014; Whitehead et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of SUDs in the older adult population is low compared with other age groups; however, the proportional admission rates into substance use treatment programs for older adults more than doubled between 2000–2012. [58] Alcohol is the primary substance of abuse for older adults (64% of admissions), though the admission rates for other substances, including opioids and cannabis have increased sharply by 221% and 150% respectively among older adults. There are also concerning data suggesting that older adults develop SUDs without a past history of abuse, since half of individuals in treatment report that their initiation of substance use occurred after 25 years old.…”
Section: Older Adults (Approximately ≥55 Years Old)mentioning
confidence: 99%
“…There are also concerning data suggesting that older adults develop SUDs without a past history of abuse, since half of individuals in treatment report that their initiation of substance use occurred after 25 years old. [58] Older adults may be at an increased risk of substance use initiation because of the changes that occur with this developmental period such as having fewer daily responsibilities, transitioning to retirement, restructuring or loss of social relationships, and deteriorating physical and mental health, which may further reduce health-related quality of life and increase opportunities for medication misuse. [24]…”
Section: Older Adults (Approximately ≥55 Years Old)mentioning
confidence: 99%
“…The 2019 NSDUH showed that 74.3% of individuals aged 50 + with a serious mental illness received any type of treatment, including individual or group, outpatient, or inpatient care (SAMHSA, 2020a). Substance use treatment admission data (Treatment Episode Data Set; TEDS: https://www.samhsa.gov/data/datawe-collect/teds-treatment-episode-data-set) also show ed that the proportions of older adults (aged 55+) seeking treatment for the first time for alcohol use disorder and for illicit drug use increased over the past decade (Chhatre, Cook, Mallik, & Jayadevappa, 2017;Huhn, Hobelmann, Ramirez, Strain, & Oyler, 2019). However, the rate of substance use treatment among this age group is much lower than the rate of mental disorder treatment.…”
Section: Introductionmentioning
confidence: 99%